What Gaze Fixation and Pupil Dilation Can Tell Us About Perceived Differences Between Abstract Art by Artists Versus by Children and Animals. (November 2015) - Alvarez, Sergio A.; Winner, Ellen; Hawley-Dolan, Angelina; Snapper, Leslie
People with no arts background often misunderstand abstract art as requiring no skill. However, adults with no art background discriminate paintings by abstract expressionists from superficially similar works by children and animals. We tested whether participants show different visual exploration when looking at paintings by artists' versus children or animals. Participants sat at an eye tracker and viewed paintings by artists paired with "similar" paintings by children or animals, and were asked which they preferred and which was better. Mean duration of eye gaze fixations, total fixation time, and spatial extent of visual exploration was greater to the artist than child or animal images in response to quality but not preference. Pupil dilation was greater to the artist images in response to both questions and greater in response to the quality than preference question. Explicit selections of images paralleled total fixation times: Participants selected at chance for preference, but selected the artist images above chance in response to quality. Results show that lay adults respond differently on both an implicit as well as explicit measure when thinking about preference versus quality in art and discriminate abstract paintings by artists from superficially similar works by children and animals, despite the popular misconception by the average viewer that "my kid could have done that."